Studying the effect of pressure in the elastic field and the plastic field of soil on some of its physical properties and on the productivity of the soybean crop - قادرو اسامه; جهاد ابراهيم; ربيع زينة; أولا قاجو (Latakia University Journal -Biological Sciences Series, 2024)
This research was conducted within the agricultural scientific research center in Latakia (stakhiris station) for the year 2022, where different levels of pressure applied to Celtic clay soils were used (0 – 163 – 216 - 297 KPA), and at two different levels of humidity (20-28% by weight). The results showed the obvious and significant effect of soil compression in the bulk density of the soil, in addition to the decrease in the size of the total porosity by increasing the pressure, noting that the effect of pressure was decreasing with depth, as the compression of the soil in the surface layer (5-20 cm) led to an increase in the bulk density by 0.16 g/cm3 at a pressure of 163 KPA and to an increase of 0.26 g/cm3 at a pressure of 297 KPA and moisture in the pressure of 297 KPA contributed to an increase in the bulk density by 0.39 g/cm3 at a humidity of 28% by weight.It is also observed at depth (5-20 CM) relative to pores whose diameters (0.2 – 10) microns, which are the pores that contain the water available to the plant, they decreased with increasing pressure from 17.45% in the treatment without pressure and at a humidity of 20% by weight to 13.26% at a pressure of 297 KPA and with increasing humidity during compression the size of these pores decreases .The results showed a significant decrease in soybean productivity with increased pressure and humidity during compression, where the decrease was by 56.88 kg/DN at a pressure of 163 KPA and by 164.21 kg/DN at a pressure of 297 KPA, compared to the treatment without pressure.